PROSPEK PENGEMBANGAN TECHNO PARK BERBASIS PENGOLAHAN HASIL PERIKANAN DI KOTA KENDARI - Azwar Sidiq; Andi Irwan Nur; Sjamsu Alam Lawelle; Roslindah Daeng Siang; Nurdiana Azis (Program Studi Agrobisnis Perikanan, Fakultas Perikanan dan Ilmu Kelautan, UHO, 2017)
The purpose of this study was to determine the potential of the fisheries product processing industry and to find out the technological requirements for the development of the processing industry in Kendari City. In aggregate capture fisheries production in Kendari City continues to increase from year to year. Dominant capture fisheries commodity production from the species of skipjack and tuna fish. In 2013 Kendari City had fishery production of 31,025.42 tons which was previously 28,186.83 tons. Regarding the availability of raw materials, the increase in fisheries production provides an opportunity for the household scale processing industry around it to increase its production volume. Based on the results of the study, there were 21 community groups engaged in processing fishery products in Kendari City. Most of the fishery product processing industry activities are spread around Kendari Ocean Port, which includes the villages of Talia, Petoaha, Tondongeeu, Poasia, Lapulu and Puday. Support for technology inputs and production activities is supported by the availability of adequate energy sources and human resources that are urgently needed in the development of Techno Park.